Ethics and epidemics - Balint, John (Advances in bioethics, 2006)
"The Advances in Bioethics" series is devoted to publishing collections of original papers and multi-authored volumes that advance the field of bioethics either by exploring new areas, or by taking new approaches to traditional areas. Although the series is published in English, its scope is international, and manuscripts are welcome from authors throughout the world. Divided into three sections this volume covers: Human Rights, Public Safety, and Public Policy; Practitioner Responsibilities During Times of Epidemics; Global Dimensions of Epidemics - each chapter in the book goes in depth to discuss the issues surrounding the topic in question and combines a theoretical thought process with practical application.